Haemocorrection in patients with malignant cerebral tumors - R. Yu. Seliverstov; V. Ye. Olyushin; V. A. Shatrov; A. F. Gurchin; K. P. Gaydayenko (Бюллетень сибирской медицины)
The goal of the research was studying the clinical-laboratory manifestations of toxemic and complex immune syndromes in patients with malignant cerebral tumors, and also studying the possibilities of correction of such syndromes by means of the programs for infusion-desintoxication therapy in combination with plasmapheresis. Basic biochemical substrates of toxemia and complex immune syndrome are oligopeptides, substances of nonprotein nature (of high, low and average molecular weight) and circulating immune complexes. Plasmapheresis provides for their excretion, which allows to reduce the degree of autoimmune aggression and toxemia effectively. Application of haemodilution and preliminary-prepared autohaemocomponents for compensation of blood loss at surgical interventions, promotes for decrease of toxemia manifestations and complex immune syndrome in the nearest post-surgery term.